Paro Hidup dan Keusangan Literatur Pada Jurnal Literatify tahun 2020-2024 - Trysnawati, Ayu; Nisa, Andi Khaerun (UPT Perpustakaan UIN Alauddin Makassar, 2025)
Literatify Journal is an academic journal that publishes issues related to the development of libraries. This journal is officially published by the Library of UIN Alauddin Makassar. One of the methods that can be used to calculate the half-life and obsolescence of literature is through a bibliometric study. This is necessary as a consideration for determining the relevance and usage period of references in scientific works. This study employed a quantitative research approach. The population in this research consists of all citations referenced in Literatify Journal articles that include publication years. Based on the analysis of 46 articles with a total of 405 citations, the half-life of Literatify Journal publications from 2020 to 2023 was found to be 7 years. Among these citations, 145 (36%) were considered obsolete, while 260 (64%) were considered current. Based on these findings, it is recommended that future scientific works refer to literature published no more than 7 years prior to the date of writing.